2015
DOI: 10.1016/j.sbspro.2015.01.403
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Leadership Styles on Job Satisfaction and Mediating Role of Perceived Organizational Politics

Abstract: The present study aims to investigate the impact of leadership styles on job satisfaction and to see if perceived organizational politics has a mediating role or not. In this study descriptive research design was used and a quantitative research was conducted. The sample of this study was selected through non-probability convenience sampling. Research finding revealed that transformational leadership has a positive impact on job satisfaction and transactional leadership has a negative impact on job satisfactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
128
1
20

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(157 citation statements)
references
References 16 publications
8
128
1
20
Order By: Relevance
“…Rad and Yarmohammadian (2006) found a significant correlation between use of leadership behavior and employee job satisfaction. This finding was further supported by Saleem (2015). In a study conducted among school teachers, Bogler (2001) found that principal's transformational leadership affected teacher's satisfaction both directly and indirectly.…”
Section: Does Ceo Leadership Style Matter?mentioning
confidence: 71%
See 1 more Smart Citation
“…Rad and Yarmohammadian (2006) found a significant correlation between use of leadership behavior and employee job satisfaction. This finding was further supported by Saleem (2015). In a study conducted among school teachers, Bogler (2001) found that principal's transformational leadership affected teacher's satisfaction both directly and indirectly.…”
Section: Does Ceo Leadership Style Matter?mentioning
confidence: 71%
“…Various scholars (e.g., Bogler, 2011;Rad & Yarmohammandion, 2006;Saleem, 2015;Voon, Lo, Ngui & Ayob, 2011) reported significant relationship of transactional and transformation leadership style with employee job satisfaction. In their comprehensive review of relationship between leadership and job satisfaction, Belias and Koustelios (2014) concluded that leadership style is an important antecedent of job satisfaction.…”
Section: Control Variablesmentioning
confidence: 99%
“…The finding of transformational leadership style having positive association with job satisfaction through the inspiring and motivating behaviour of transformational leader (Saleem, 2015). Followers are encouraged and motivated to take on more responsibility and autonomy by transformational leaders (Emery & Barker, 2015), thereby it enhance employees' sense of accomplishment and satisfaction with their job is enhanced.…”
Section: Discussion On the Major Findings And Implicationmentioning
confidence: 99%
“…Literatürde, iş tatmininin müşteri tatmini (Torres ve Kline, 2006), iş motivasyonu ve iş stresi (Chen vd., 2012), demografik değişkenler (Lam, Zhang ve Bau, 2001;Clark, 1997;Öztürk ve Alkış, 2011), örgütsel çatışma (Üngüren, Cengiz ve Algür, 2009), narsizim (Timuroğlu ve İşcan, 2008), örgüt kültürü (Rızaoğlu ve Ayyıldız, 2008) ve liderlik (Arzi ve Farahbod, 2014;Bogler, 2001;Ugboro ve Obeng, 2000;Saleem, 2015) gibi değişkenlerle ilişkilerinin araştırıldığı da görülmektedir.…”
Section: İş Tatminiunclassified